2019
DOI: 10.5546/aap.2019.eng.94
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for the follow-up of children with leg length discrepancy: expert consensus

Abstract: Leg length discrepancy is when the length of one leg is different from the other, and is a common reason for consultation at the pediatrician's and pediatric orthopedist's office. The objective of this study was to develop recommendations for the follow-up, pre-surgical planning, and treatment of children with leg length discrepancy based on expert consensus. Material and methods. The Delphi method was used. A coordinating group selected a panel of experts, designed and analyzed each of the rounds of consultat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…For example, CT scanogram is the best method to measure LLD when knee flexion is greater than 30 degree (18). Otherwise, the results of radiologic studies were similar (18)(19)(20)(21). Furthermore, there is no difference between standing and supine radiologic measurements in lower limbs in the case of mechanical axis deviation less than 20mm (20).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, CT scanogram is the best method to measure LLD when knee flexion is greater than 30 degree (18). Otherwise, the results of radiologic studies were similar (18)(19)(20)(21). Furthermore, there is no difference between standing and supine radiologic measurements in lower limbs in the case of mechanical axis deviation less than 20mm (20).…”
Section: Discussionmentioning
confidence: 97%
“…In previous studies, the accuracy of radiologic methods has been reported and compared. For example, CT scanogram is the best method to measure LLD when knee flexion is greater than 30 degree (18). Otherwise, the results of radiologic studies were similar (18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 97%